Ανάπτυξη κώδικα MATLAB στην επξεργασία δεδομένων από μοριακά δυναμική - Χαραλάμπους, Φεβρωνία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
Within the scope of this dissertation, entitled “"Development of MATLAB code for processing data by Molecular Dynamics (Theoretical Vibrational Spectroscopy)”, a MATLAB code was developed in order to determine the vibrational spectrum of atmospheric gases: Carbon monoxide (CO), methanol (CH3OH), glyoxal (CHOCHO), as well as intermediate products of the respiration process; the ferryl-oxo intermediate of the reduction of atmospheric 16Ο2 and 18Ο2 to water by cytochrome c oxidase from. Initially, we present the literature for the MATLAB code development and basic mathematical themes on Fourier Series, Integral and Fourier Transforms. We focused on the Discrete and Fast Fourier Transform as well as the Velocity Autocorrelation Function, a direct output of the Molecular Dynamics Calculations. The above methods were implemented into the MATLAB code, which, loads a time-speeds series out of a Molecular Dynamics Calculation, , it determines their Velocity Autocorrelation Function and subsequently the vibrational spectrum of the system. . The goal is to determine the best sampling for the velocities of the system atoms, for diverse systems, throughout a Molecular Dynamics Simulation, in order to produce an accurate theoretical vibrational spectrum of the system; absorption values that do not deviate significantly from the experiment. Therefore, this dissertation presents results that will help in saving computer memory during the calculation, as the sampling rate is a crucial drawback in the speed and storage needs of the Molecular Dynamics (MD) Calculations We determined that this sampling rate is system-specific and should be calculated before the MD production runs
Keywords: MATLAB code; Atmospheric gases